2003
DOI: 10.1177/000348940311200115
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Cholinergic Receptor Expression in the Human Nasal Mucosa

Abstract: Twenty-four nasal mucosa specimens were obtained from the inferior or middle turbinates of 6 normal subjects and 18 patients with chronic sinusitis, inflammatory polyp formation, or sinus allergies. Reverse transcription-polymerase chain reaction analysis was used to identify the non-neuronal nicotinic cholinergic receptor (nAChR) subunits that were expressed in the nasal mucosa. Collectively, transcripts for alpha (alpha1, alpha2, alpha3, alpha4, alpha6, alpha7) and beta (beta2, beta3, beta4) nAChR subunit ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…One explanation for this may be that, unlike nicotine's pharmacologic effects, nicotine's airway sensory effects are not mediated by nicotinic acetylcholine receptors; rapid desensitization of nicotinic acetylcholine receptors may underlie acute tolerance, so a nonreceptor-mediated process could potentially circumvent acute tolerance. This is unlikely, however, since the airway expresses an abundance of nicotinic acetylcholine receptors (Wang et al, 2001;Keiger et al, 2003;Proskocil et al, 2004) and it has been shown that blockade of nicotinic acetylcholine receptors significantly reduces the airway sensory effects of smoking (Lee et al, 1993;Rose et al, 1999a,b). An alternative explanation is that the airway sensations stimulated by nicotine may be transduced by an isoform of the nicotinic acetylcholine receptor that is not susceptible to rapid desensitization, or does not undergo as complete a desensitization as the receptors that mediate nicotine's pharmacologic effects.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this may be that, unlike nicotine's pharmacologic effects, nicotine's airway sensory effects are not mediated by nicotinic acetylcholine receptors; rapid desensitization of nicotinic acetylcholine receptors may underlie acute tolerance, so a nonreceptor-mediated process could potentially circumvent acute tolerance. This is unlikely, however, since the airway expresses an abundance of nicotinic acetylcholine receptors (Wang et al, 2001;Keiger et al, 2003;Proskocil et al, 2004) and it has been shown that blockade of nicotinic acetylcholine receptors significantly reduces the airway sensory effects of smoking (Lee et al, 1993;Rose et al, 1999a,b). An alternative explanation is that the airway sensations stimulated by nicotine may be transduced by an isoform of the nicotinic acetylcholine receptor that is not susceptible to rapid desensitization, or does not undergo as complete a desensitization as the receptors that mediate nicotine's pharmacologic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine receptor gene expression in the nasal mucosa has been demonstrated [38], and perhaps nicotine receptor activation somehow influences the mucosal compliance. One study found that smoking cessation in patients with chronic rhinitis did not improve the minimal cross-sectional area after 20 weeks when smoking was substituted with nasal nicotine; unfortunately, no controls were enrolled [39].…”
Section: Smoking and Its Effect On The Nasal Mucosamentioning
confidence: 99%
“…Finally, other nAChR subtypes may underlie behavioral sex differences. For example, a study found sex differences in b 3 -nAChR expression in the nasal mucosa of human subjects (48). Future studies are needed to evaluate these alternatives.…”
Section: The Effect Of Sex On B 2 -Nachr Availabilitymentioning
confidence: 99%